Moderasi Beragama dalam Masyarakat 5.0: Analisis Konsep Berdasarkan Surat Al-Hujurat Ayat 13 - Husni, Radhiatul; Utomo, Edi; Rizqa, Miftahir; Husna, Rohaniatul (SURAU : Journal of Islamic Education, 2023)
AbstractThis research discusses the concept of religious moderation in the context of Society 5.0, using the analysis of Surah Al-Hujurat Verse 13 in the Quran as a foundation. Society 5.0 refers to an era where information and communication technology significantly transform social, economic, and cultural dynamics. In this context, it is important to understand how religious values, particularly in Islam, can be applied appropriately and relevantly. Surah Al-Hujurat Verse 13 is one of the verses that highlights the principles of religious moderation in Islam. The results of this research are as follows: 1) the analysis of religious moderation concept, with reference to Verse 13 of Surah Al-Hujurat, can be interpreted as doctrines that uphold values and principles aligned with the vision of Society 5.0, prioritizing diversity, inclusivity, morality, and collaboration in creating a harmonious and sustainable society. 2) religious moderation can play a crucial role in maintaining social harmony and contributing to the creation of a more harmonious society. 3) religious moderation based on Surah Al-Hujurat Verse 13 can help to form an inclusive society, where diverse perspectives and beliefs are respected and accepted.Â AbstrakPenelitian ini membahas konsep moderasi beragama dalam konteks masyarakat 5.0 dengan menggunakan analisis Surat Al-Hujurat Ayat 13 dalam Al-Quran sebagai landasan. Masyarakat 5.0 merujuk pada era di mana teknologi informasi dan komunikasi mengubah dinamika sosial, ekonomi, dan budaya secara signifikan. Dalam konteks ini, penting untuk memahami bagaimana nilai-nilai agama, khususnya dalam Islam, dapat diterapkan dengan tepat dan relevan. Surat Al-Hujurat Ayat 13 merupakan salah satu ayat yang menyoroti prinsip-prinsip moderasi beragama dalam Islam. Hasil dari penelitian ini adalah 1) analisis konsep moderasi beragama dengan mengacu pada ayat 13 dari Surat Al-hujurat dapat dipahami sebagai ajaran yang mendukung nilai-nilai dan prinsip-prinsip yang juga relevan dengan visi masyarakat 5.0 yang mengutamakan keragaman, inklusivitas, moralitas, dan kolaborasi dalam menciptakan masyarakat yang harmonis dan berkelanjutan. 2) moderasi beragama dapat berperan penting dalam memelihara harmoni sosial dan berkonstribusi pada terciptanya masyarakat yang lebih harmonis. 3) moderasi beragama yang berlandaskan pada Surat Al-Hujurat ayat 13 dapat membantu membentuk masyarakat yang inklusif, dimana beragam pandangan dan kepercayaan dihormati dan diterima.